THE DOMINANCE OF DARK ENERGY LEADS TO REDUCTION OF THE ENTROPY OF GALAXIES FLOW AND ENTROPY OF THE UNIVERSE - Bukalov О. V. (Одеські астрономічні публікації, 2016)
The existence of the Hubble flow recession of galaxies in terms of dominance of dark energy density, vacuum energy, reduces the gravitational entropy of clusters of galaxies, reducing the gravitational entropy of the Universe as a whole. Global dominance of dark energy leads to a decrease in entropy of the Universe within the cosmic event horizon